Cardiovascular complications of chemotherapy: A synopsis - Steingo, Len (SA Heart Journal, 2017)
It is important to identify chemotherapy-related cardiotoxicity as it may impact on the overall survival of cancer patients. The various forms of cardiotoxicity encountered during and after chemotherapy for cancer, include impaired left ventricular function leading to cardiomyopathy (CMO), myocardial ischaemia, hypertension (HTN), thromboembolic states, bradycardia and prolongation of the QT interval predisposing to ventricular arrhythmias. The relationships between specifi c chemotherapeutic agents and the occurrence of these complications are discussed, highlighting the need for close collaboration between oncologists and cardiologists.